Avaliação experimental da sincronização por densificação de grupos de pedestres em passarelas - Araújo Junior, Moacir Carlos (2008)
Footbridges are special works of art, present in large urban centers and along the highways. They are built above the roads to improve the safety of pedestrians and facilitate the flow of traffic, since they eliminate the points of conflict between pedestrians and vehicles. The occurrence of the phenomenon lock-in has implied the closing for repair of footbridges subject to dynamic loading induced by crowds of walking pedestrians. This is because the synchronization between the movement of pedestrians and the displacement of the structure has resulted in the occurrence of excessive vibration, when the frequency of excitation generated due to walking is close to the natural frequency of the footbridge. Despite several works about the lock-in, little has been concluded to try to develop a mathematical model to represent the onset of the phenomenon. In principle, another type of synchronization, which occurs among pedestrians, due to densification in crowd situations, would start rising vibrations in the structure, initiating the lock-in. However, there is a lack of experimental data in the literature to prove that theory. An experimental study on the synchronization between pedestrians due to densification was carried out in this research. Experimental tests were conducted on a prototype footbridge with different densities of pedestrians. For the densities investigated (0,3, 0,7 and 0,9 pedestrians/m²) with the pedestrian walking with their natural pacing rate, no evidence of synchronization was found. Tests were also conducted with induced pacing rate, to check the robustness of the methodology used. The results showed that the procedure adopted was valid and can be applied to other densities of interest.